A Rare Case of Jejunal Diverticular Perforation in an Acute Abdomen - Banerjee, Divya Jyoti; Chauhan, Himesh (Medicine and Medical Research: New Perspectives Vol. 8, 2024)
Jejunoileal diverticula (JID), the least common of small bowel diverticula, has a rare prevalence with an incidence of <5% in imaging. JID are often identified on exploratory laparotomy or laparoscopy for other indications or the evaluation of chronic or acute symptoms. Jejunal diverticula are acquired pseudodiverticula that occur due to the herniation of the mucosa and submucosa through the weakest side of the muscularis propria of the bowel wall. Perforation of inflamed diverticula is a rare phenomenon that needs immediate operative intervention, an exploratory laparotomy along resection and anastomosis. This study reports the case of a 50-year-old female with jejunal diverticular perforation. The patient presented with complaints of generalized abdominal pain associated with abdominal distension, constipation, and vomiting. Upon examination, generalized abdominal tenderness, guarding, and rigidity were noted. Ultrasound findings suggested a sealed bowel/diverticular perforation with localized peritoneal collection. The patient was started on intravenous (IV) fluids and broad-spectrum antibiotics. The patient was taken for exploratory laparotomy which showed a jejunal diverticulum along with perforation. It was decided to do resection and anastomosis of the affected segment. The follow-up was uneventful. Since perforation of the jejunal diverticula is a rare phenomenon, the diagnosis needs to be considered in patients presenting with an acute abdomen. Although the perforation of the Jejunal diverticula is a rare phenomenon affecting the elderly population, the diagnosis needs to be considered in patients presenting with an acute abdomen.